2013
DOI: 10.4049/jimmunol.1202223
|View full text |Cite
|
Sign up to set email alerts
|

Human Invariant NKT Cell Subsets Differentially Promote Differentiation, Antibody Production, and T Cell Stimulation by B Cells In Vitro

Abstract: Invariant natural killer T (iNKT) cells can provide help for B cell activation and antibody production. Since B cells are also capable of cytokine production, antigen presentation and T cell activation, we hypothesized that iNKT cells will also influence these activities. Furthermore, subsets of iNKT cells based on CD4 and CD8 expression that have distinct functional activities may differentially affect B cell functions. We investigated the effects of co-culturing expanded human CD4+, CD8α+ and CD4−CD8α− doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 58 publications
(119 reference statements)
1
49
1
1
Order By: Relevance
“…This finding was later confirmed using fresh human iNKT cells [180]. In our own work, we investigated the effects of co-culturing expanded human CD4 + , CD8a + and CD4 À CD8a À iNKT cells with autologous peripheral B cells in vitro and found that all iNKT cell subsets induced IgM, IgA and IgG release by B cells by a mechanism that required CD1d but not added glycolipid, such as a-GC [181]. All iNKT cell subsets induced the expression of CD40, CD86 and HLA-DR by B cells, but iNKT cell-matured B cells were less able to drive proliferation of autologous and alloreactive conventional T cells than B cells cultured in the absence of iNKT cells.…”
Section: Other Unconventional T Cells Bridging Innate and Adaptive Immentioning
confidence: 79%
See 1 more Smart Citation
“…This finding was later confirmed using fresh human iNKT cells [180]. In our own work, we investigated the effects of co-culturing expanded human CD4 + , CD8a + and CD4 À CD8a À iNKT cells with autologous peripheral B cells in vitro and found that all iNKT cell subsets induced IgM, IgA and IgG release by B cells by a mechanism that required CD1d but not added glycolipid, such as a-GC [181]. All iNKT cell subsets induced the expression of CD40, CD86 and HLA-DR by B cells, but iNKT cell-matured B cells were less able to drive proliferation of autologous and alloreactive conventional T cells than B cells cultured in the absence of iNKT cells.…”
Section: Other Unconventional T Cells Bridging Innate and Adaptive Immentioning
confidence: 79%
“…Additionally, CD4 + iNKT cells induced expansions of cells with phenotypes of regulatory B cells. Therefore, human iNKT cell subsets may differentially promote and regulate antibody production and T cell activation by B cells [181].…”
Section: Other Unconventional T Cells Bridging Innate and Adaptive Immentioning
confidence: 99%
“…13,14 iNKT cells are a small but critical T-cell population involved in the B-cell response to glycolipid antigens via CD1d, a major histocompatibility complex-like molecule. 14 iNKT cells promote B-cell proliferation, B memory responsiveness, plasma cell generation and antibody production.…”
mentioning
confidence: 99%
“…14 iNKT cells promote B-cell proliferation, B memory responsiveness, plasma cell generation and antibody production. 14,15 Their relative absence in common variable immunodeficiency may contribute to both B-cell defects and hypogammaglobulinemia. Recent studies suggest that iNKT can stimulate B-cell proliferation and antibody production through cell-cell contact, probably due to the expression of stimulatory glycolipid self-antigens on B cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation